方程[img=170x26]1803e29208c23a3.png[/img]所确定得隐函数在[img=44x18]1803e292113b404.png[/img]处的导数[img=88x44]1803e29218dcdbd.png[/img]
A: 1/2
B: -1/2
C: 0
D: 1
A: 1/2
B: -1/2
C: 0
D: 1
举一反三
- 由方程[img=120x23]1803e28f37fcfa6.png[/img]所确定的隐函数[img=66x25]1803e28f420afe9.png[/img]在点[img=44x18]1803e28f4a59abb.png[/img]对应点处的导数( ) A: 1 B: -1 C: 1/e D: -1/e
- 由方程[img=120x19]17e43c83ebda8f7.jpg[/img]确定变量 y 为 x 的函数在 [img=34x14]17e435d908d29fd.jpg[/img]处导数为()。 A: 0 B: 1 C: -1 D: 2
- 由方程[img=120x19]17da5f94b4bf911.jpg[/img]确定变量 y 为 x 的函数在 [img=34x14]17da424370cf4cb.jpg[/img]处导数为()。 A: 0 B: 1 C: -1 D: 2
- 求由方程[img=146x26]1803d352f44c205.png[/img]所确定的隐函数在[img=44x18]1803d352fce06bf.png[/img]处的导数[img=53x44]1803d35305f0a03.png[/img] A: 1 B: 0 C: [img=9x43]1803d3530e2d141.png[/img] D: -1
- 求由方程[img=134x41]17da65377a0f91e.png[/img]所确定的隐函数[img=91x50]17da653782b7d9a.png[/img]的导数。 ( ) A: x*exp(y/x) B: x*exp(y/x)*(1/x + y/(x^2*exp(y/x))) C: x*exp(y/x)*(1/x + y/(x^2*exp(y/x)))+x*exp(y/x) D: (1/x + y/(x^2*exp(y/x)))